Implantable cardioverter‐defibrillator in Brugada syndrome: long‐term follow‐up - El-Battrawy, Ibrahim; Roterberg, Gretje; Liebe, Volker; Ansari, Uzair; Lang, Siegfried; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Clinical cardiology, 2019)
Background - Brugada syndrome (BrS) is associated with sudden cardiac death (SCD). Although implantable cardioverter‐defibrillator (ICD) implantation is recommended, the long‐term outcomes and follow-up data with regard to ICD complications have led to controversy.